DOS 6.0 for Personal Computers - DESIDOC, Director (DESIDOC Journal of Library & Information Technology, 2002)
MS DOS from Microsoft Corporation,USA has been the most widely used operating system for personal computers all over the world. In 1993, the company came out with the latest version DOS 6.0 which is now also available in Indian market. The earlier 5.0 version of DOS had the ability to run in the high memory area of RAM, making programs to run faster and more efficiently. It had an improved graphical interface-MS DOS shell which could manage programs and switch between them. It had two new commands-unformat and undelete-for data security; and online help for all MS DOS commands, MS DOS shell, and for MS DOS Editor which allowed users to easily create and modify text files. The version had the capability to create larger disk partitions upto 2 GB and support 2.88 MB floppy diskettes. http://dx.doi.org/10.14429/dbit.14.1.3089